THE EFFECT OF CABBAGE EXTRACT ON KIDNEY FUNCTION IN MALE RATS EXPOSED TO CARBON TETRACHLORIDE - Hala Hameed Majeed; Iktefa Abdul Hamid Mohammed Saeed; Loay H. Ali (Scholar Express Journals, 2023)
The aim of the current study is to determine the preventive effect of the hydrological extract of green and red coiled plant leaves on kidney function by measuring urea, creatinine and uric acid in male white rats. A 50 of male Swiss rats were used, weighting 165- 210 grams, distributed to 10 groups and divided into the following groups: The olive oil dose was given by tubular feeding of 0.3 ml per rat, the second group: it was given 0.2 ml CCl4 by peritoneal injection, group III: CCl4 0.2 ml injected by peritoneal injection for four weeks after which I gave the water extract of 1 ml green cabbage, Group IV: CCl injected the 4 with 2.0 ml by peritoneal injection for four weeks and then gave the water extract of 1 ml red cabbage, Group V: CCl injected 4 0.2 ml by peritoneal injection for four weeks and then gave water extract for green and red cabbage by 1 ml Group VI: salmarine herb was given 1 mg per rat. Group VII: 1 ml green cabbage water extract was given. Group VIII: 1 ml red cabbage water extract, Group IX: I gave the water extract of the green and red cabbage by 1 ml, group X: The control group was given 3 ml distilled water and by means of the infectious feeding tube with the provision of leaf, then the blood samples were withdrawn and the serum was separated by common methods and tested for the physiological and chemical variables
Keywords: Cabbage; Urea; Creatinine; Uric acid; Kidney